2(x+3)(x+3)-9=89

Simple and best practice solution for 2(x+3)(x+3)-9=89 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+3)(x+3)-9=89 equation:


Simplifying
2(x + 3)(x + 3) + -9 = 89

Reorder the terms:
2(3 + x)(x + 3) + -9 = 89

Reorder the terms:
2(3 + x)(3 + x) + -9 = 89

Multiply (3 + x) * (3 + x)
2(3(3 + x) + x(3 + x)) + -9 = 89
2((3 * 3 + x * 3) + x(3 + x)) + -9 = 89
2((9 + 3x) + x(3 + x)) + -9 = 89
2(9 + 3x + (3 * x + x * x)) + -9 = 89
2(9 + 3x + (3x + x2)) + -9 = 89

Combine like terms: 3x + 3x = 6x
2(9 + 6x + x2) + -9 = 89
(9 * 2 + 6x * 2 + x2 * 2) + -9 = 89
(18 + 12x + 2x2) + -9 = 89

Reorder the terms:
18 + -9 + 12x + 2x2 = 89

Combine like terms: 18 + -9 = 9
9 + 12x + 2x2 = 89

Solving
9 + 12x + 2x2 = 89

Solving for variable 'x'.

Reorder the terms:
9 + -89 + 12x + 2x2 = 89 + -89

Combine like terms: 9 + -89 = -80
-80 + 12x + 2x2 = 89 + -89

Combine like terms: 89 + -89 = 0
-80 + 12x + 2x2 = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(-40 + 6x + x2) = 0

Factor a trinomial.
2((-10 + -1x)(4 + -1x)) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(-10 + -1x)' equal to zero and attempt to solve: Simplifying -10 + -1x = 0 Solving -10 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -1x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + -1x = 0 + 10 -1x = 0 + 10 Combine like terms: 0 + 10 = 10 -1x = 10 Divide each side by '-1'. x = -10 Simplifying x = -10

Subproblem 2

Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4

Solution

x = {-10, 4}

See similar equations:

| 2p^2+15p=22 | | A=4a+6 | | 3y+2x-7= | | 6x+y=125 | | 5x=11x+24 | | 2(4x-1)+2(x+2)=x+7+4x+4+4x+6 | | 3.03(2w+4.3)=-20.07 | | 2p^2+14p+12=0 | | 3p^2+14p+12=0 | | -4=-7+w | | 8-5x=8-2x | | -6(12-15)+2x^3= | | 2w+2.5=0.5w | | 5x+2-3x=14 | | 2x^2+23x-8=0 | | 3x+(2x+6)= | | 9(z-6)= | | 18x+2=x+8+x-6 | | 17(x+3)=6(x+7)+31 | | 3x(-4)+(52+-4*2)-(-9.82)= | | 8(q+9)= | | -4(5p+4)-44=3(2p+6) | | 4x-11y=3x+7 | | -8(y+4)=-7y-5 | | -4(5t-4)+8t=5t-2 | | 6n-7+8n+2=23 | | 3-7n+5n=32-67 | | Cos(x)-2x=0 | | -53+10y+6=5(3y-4)-7 | | 12(y+4)=4(2y+1)+4y | | 3x(-4)+(52+-4*2)= | | 8a+6-8a+7= |

Equations solver categories